Minimum information reporting in bio-nano experimental literature - Faria, Matthew; Björnmalm, Mattias; Thurecht, Kristofer J; Kent, Stephen J; Parton, Robert G; Kavallaris, Maria; Johnston, Angus P R; Gooding, J Justin; Corrie, Simon R; Boyd, Ben J; Thordarson, Pall; Whittaker, Andrew K; et al. (Nature nanotechnology, 2018)
Studying the interactions between nanoengineered materials and biological systems plays a vital role in the development of biological applications of nanotechnology and the improvement of our fundamental understanding of the bio-nano interface. A significant barrier to progress in this multidisciplinary area is the variability of published literature with regards to characterizations performed and experimental details reported. Here, we suggest a 'minimum information standard' for experimental literature investigating bio-nano interactions. This standard consists of specific components to be reported, divided into three categories: material characterization, biological characterization and details of experimental protocols. Our intention is for these proposed standards to improve reproducibility, increase quantitative comparisons of bio-nano materials, and facilitate meta analyses and in silico modelling.